Filling in the Blanks: Josephus'Version of the Campaign of the Three Kings, 2 Kings 3 - Begg, Christopher 1950- (1993)
This article offers a detailed study of Josephus' account of the campaign of the three kings in Antiquities of the Jews 9,29—43 in relation to its Biblical source, 2 Kgs 3:4—27 (as witnessed by MT, two Greek versions, i.e. Codex Vaticanus and the minuscules representative of the (proto-)Lucianic recension, and Targum Jonathan on the Former Prophets). After discussion of the respective contexts of the episode in Josephus and the Book of Kings, the article examines in turn the five parallel segments into which the Josephan and Biblical narratives may be divided up. Throughout the investigation, special attention is given to the identification of "divergences" between Josephus and his Vorlage, as well as the occasions for and effects of those divergences. A concluding synthesis points out, e.g., that Josephus' account differs from the Biblical one especially in its "filling in the latter's blanks" — hence the title of the study.
Keywords: Josephus, Flavius -- 37-100; Bibel